Crystal Ice / Ely Soraya Noriozaman ... [et al.] - Noriozaman, Ely Soraya; Zainordin, Zainor Hanee; Pamidi, Safiah; Mat Nor, Nor Arbaeyah; Saidin, Hafiz Firdaus (Faculty of Hotel and Tourism Management, 2002)
Crystal Ice is a place where you can feel relax and casual at. Actually, Crystal Ice is a small kiosk that specializing in a variety of flavoured ice blended that includes coffee, chocolate, vanilla, mocha, cappuccino, yogurt, and others fresh fruits ice blended. We have used a flavors powder and fresh fruits for our ice blended. We also mix the ice blended with pearl tapioca, jelly grass, and basil seed. We also give the opportunity to our customers to choose two types of any flavored and mix them together.